Platelet‐rich fibrin‐based matrices to improve angiogenesis in an in vitro co‐culture model for bone tissue engineering. (30th August 2017) - Dohle, Eva; El Bagdadi, Karima; Sader, Robert; Choukroun, Joseph; James Kirkpatrick, C.; Ghanaati, Shahram
Abstract: In the context of prevascularization strategies for tissue‐engineering purposes, co‐culture systems consisting of outgrowth endothelial cells (OECs) and primary osteoblasts (pOBs) have been established as a promising in vitro tool to study regeneration mechanisms and to identify factors that might positively influence repair processes such as wound healing or angiogenesis. The development of autologous injectable platelet‐rich fibrin (PRF), which can be generated from peripheral blood in a minimal invasive procedure, fulfils several requirements for clinically applicable cell‐based tissue‐engineering strategies. During this study, the established co‐culture system of OECs and pOBs was mixed with injectable PRF and was cultivated in vitro for 24 h or 7 days. The aim of this study was to analyse whether PRF might have a positive effect on wound healing processes and angiogenic activation of OECs in the co‐culture with regard to proinflammatory factors, adhesion molecules and proangiogenic growth factor expression. Histological cell detection revealed the formation of lumina and microvessel‐like structures in the PRF/co‐culture complexes after 7 days of complex cultivation. Interestingly, the angiogenic activation of OECs was accompanied by an upregulation of wound healing‐associated factors, as well as by a higher expression of the proangiogenic factor vascular endothelial growth factor, which was evaluated both on the mRNA level as well as on the protein level. Thus, PRF might positively influence wound healing processes, in particular angiogenesis, in the in vitro co‐culture, making autologous PRF‐based matrices a beneficial therapeutic tool for tissue‐engineering purposes by simply profiting from the PRF, which contains blood plasma, platelets and leukocytes.